HIGH SELECTIVE ASYMMETRIC SYNTHESIS OF (S)-β-(N-IZOPROPYLAMINO)-α-ALANINE (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
Asymmetric addition of izopropylamine to C=C bond of NiII-complex Schiff`s base of dehydroalanine with modified chiral auxiliary (S)-N-(2-benzoilphenyl)-1-(2-chlorbenzyl)pyrrolidine-2-carboxamide was investigated and high selective method of asymmetric synthesis of non-protein amino acid (S)-β-N-izopropylaminoalanine (ee >97%) was developed.
Keywords: izopropylamine; Schiff`s base; (S)-N-(2-benzoilphenyl)-1-(2-chlorbenzyl)pyrrolidine-2-carboxamide; (S)-β-N-izopropylaminoalanine